Incidence and risk factors of leukoaraiosis from 4683 hospitalized patients: A cross-sectional study. Issue 39 (September 2017) - Lin, Qing; Huang, Wen-Qing; Ma, Qi-Lin; Lu, Cong-Xia; Tong, Sui-Jun; Ye, Jin-Hu; Lin, Hui-Nuan; Gu, Long; Yi, Ke-Hui; Cai, Liang-Liang; Tzeng, Chi-Meng
Abstract : Abstract: Leukoaraiosis (LA) refers to white matter hyperintensities or white matter lesions (WMLs) on magnetic resonance imaging (MRI) scans of the brain; this disease is associated with an increased risk of stroke, dementia, and cognitive decline. The aims of the study are to assess the incidence of LA and its associated risk factors in a Chinese population. A hospital-based cross-sectional study was conducted that included 4683 patients who were 40 years or older. Data collected included age, sex, hypertension, diabetes, smoking, drinking, homocysteine (HCY), and low-density lipoprotein cholesterol (LDL-C) levels in the blood in addition to brain MRI information. We examined the relationship of those putative risk factors with LA, LA occurrence, and LA progression through single-factor and multivariate analyses. Of the total subjects, 58.3% (2731/4683 cases) suffered from LA. LA was more frequent amongst elderly females, particularly in those older than 60, compared to men. The incidence of LA increased with age. Age, sex, hypertension, diabetes, smoking, and HCY levels all were risk factors for LA. Amongst those risk factors, both smoking and high HCY levels were associated with the onset process of LA. Moreover, the multivariate logistic analysis revealed that both drinking and abnormal LDL-C levels were positive regulators in the progression process of LA. This study revealed that the incidence of LA is high in hospitalized patients in China; moreover, age, sex, hypertension, diabetes mellitus, smoking, drinking, and abnormal HCY and LDL-C levels were found to be associated with overall LA risk, LA onset, or LA progression. These results provide insight into strategies for the prevention and treatment of LA. Abstract : Supplemental Digital Content is available in the text